The Role of Transformational Leadership, Motivation, Commitment, Discipline, and Job Satisfaction on Employee Performance - Muhamad Dafa Izulhaq; Efriyani Sumastuti; Prianka Ratri Nastiti (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to examine and analyze the influence of transformational leadership, motivation, commitment, discipline, and job satisfaction on employee performance at Bank BCA BSB. Data collection was carried out using primary data through a questionnaire technique. The population consisted of all employees of Bank BCA BSB, and using Slovin’s formula, a sample size of 334 employees was determined. The results of the study indicate that, Transformational Leadership does not influence Employee Performance. Motivation does not influence Employee Performance. Discipline has an effect on Employee Performance. Commitment also has an effect on Employee Performance. Job Satisfaction does not influence Employee Performance.